Customer Expectation vs. Satisfaction of Retail Banking Services Offered by Private Sector Banks – An Empirical Study - S. , Gowri; C. , Indhumathi (International Journal of Psychosocial Rehabilitation, 2020)
The banking industry sector is considered one of the vital contributors to the economic growth of a country. It serves as the central channel for all economic activities. The economic growth and prosperity of India have been influenced and accelerated by the expansion of the banking system. Retail banking is a major form of Indian scheduled commercial banking, which mainly involves individual customers rather than corporate clients Retail banking has immense opportunities in a growing economy like India. Some of the key economic policies focused on the retail-banking sector in India are: financial inclusion, responsible lending and access to easy finance, long-term savings, financial capability, consumer protection, regulation and financial crime prevention. Moreover, modern-day banking customers worldwide are exercising their ‘freedom of choice’ by changing their banks in search for better service and custom-tailored products. Thus, to keep the customers satisfied and meet the expectation before time, bankers are keeping changing their strategies for success their services in new age economy. Drawing relevance from the above discussions, this study aims to analyse the consumer expectation and satisfaction towards retail banking services offered by New Generation Private Sector Banks in India, as they are pioneers in offering innovative and technology-enabled retail banking services in India.